Captain Fantastic [videorecording (DVD)] - Ross, Matt; Mortensen, Viggo, 1958-; MacKay, George, 1992-; Langella, Frank; Hahn, Kathryn, 1974- (Universal Pictures Home Entertainment, 2016)
Deep in the forests of the Pacific Northwest, isolated from society, a devoted father dedicates his life to transforming his six young children into extraordinary adults. But when a tragedy strikes the family, they are forced to leave this self-created paradise and begin a journey into the outside world that challenges his idea of what it means to be a parent and brings into question everything he's taught them.